Survival and cardiac toxicity in patients with HER2‐positive, metastatic breast cancer treated with trastuzumab in routine clinical practice. Issue 1 (28th October 2019) - Vasista, Anuradha; Ryan, Luke; Naher, Sayeda; Moylan, Eugene; Stockler, Martin R; Wilcken, Nicholas; Kiely, Belinda E
Abstract: Aims: We sought to describe survival outcomes and toxicities of trastuzumab in real‐world patients with HER2‐positive, metastatic breast cancer (MBC) and compare these to a recent systematic review of clinical trials. Methods: We searched the medical records of three Sydney cancer centers for patients with HER2‐positive, MBC starting trastuzumab from January 2001 to March 2017. We recorded patient, tumor, and treatment characteristics; survival times from start of palliative trastuzumab; and rates of cardiac toxicity. Survival distribution was summarized using the following percentiles (represented scenario): 90th (worst‐case), 75th (lower‐typical), 25th (upper‐typical), and 10th (best‐case). Survival times were compared to recent review of HER2‐positive MBC randomized trials. Factors associated with survival were assessed with Cox models. Results: Characteristics of the 126 patients were: median age 53 years, ER positive cancer (50%), de‐novo metastatic disease (23%), prior adjuvant trastuzumab (15%), liver metastases (37%), and brain metastases (23%). The median duration of first‐line trastuzumab was 11 months (interquartile range, (IQR) 5–27). Survival times in months (vs the systematic review) were: 90th percentile 8 (9); 75th percentile 16 (19); and median 34 (33). Follow‐up duration was insufficient to estimate the 25th and 10th percentiles, similar to the systematic review. Liver metastases were associated with shorter survival (HR = 1.74, 95% CI, 1.1‐2.76, P  = .02). Seventy percent of patients had a baseline cardiac assessment. Five patients (3.9%) developed symptomatic cardiac toxicity, similar to clinical trials. Conclusion: Survival and cardiac toxicity rates for women starting trastuzumab in routine practice were comparable to clinical trials. Oncologists can use clinical trial data as a reference point when explaining survival outcomes to women with HER2‐positive MBC.